Design of Coconut Milk Extractor with Screw Press System - Febrina Medyanti Sinaga; Achwil Putra Munir; Saipul Bahri Daulay (Universitas Sumatera Utara, 2016)
Until now, obtain coconut milk was still obtain using conventional method which is hand pressed. Later on, manual coconut milk extractor is develop using hydrolic press system. With the development of science and technology in this modern age, people trying to create or make a new, more efficient and practical equipment. Therefore, in this research, the author tried to ease the extraction of coconut milk by designing coconut milk extractor with screw press system which has larger capacity which be more effective and efficient in coconut extraction. The coconut milk extractor worked by enter shredded coconut into hopper then shredded coconut is carried toward tubular filter contained screw press. After that the milk is produced and the dregs out separately. The results showed that the effective capacity of the equipment was 11,25 kg/hour. Primary cost was Rp. 787,022/Kg for the first year, Rp. 792,205/Kg for the second year, Rp. 797,777/Kg for the third year, Rp. 803,769/Kg for the fourth year, and Rp. 810,204/Kg for the fifth year. BEP was 1.238 Kg in the first year, 1.305 Kg in the second year, 1.377 Kg in the third year, 1.454 Kg in the fourth year and 1.537 Kg in the fifth year. The IRR was 45,54%. Keywords: equipment design, coconut milk extractor, coconut milk, screw press.